Immune response interaction of Klebsiella pneumoniae and Eimeria tenella - Al –Samrraee, Ikram Abbas Aboud (The Iraqi Journal of Veterinary Medicine, 2017)
This study aimed to investigate the immune responses (Cellular and humoral) to Klebsiella pneumoniae and Eimeria tenella by using Delayed Type Hypersensitivity Test (Skin Test) and Tube Agglutination Test in sixteen local breed rabbits. Animals were divided into four equal groups; First group was immunized subcutaneously with 1 ml (1000 µg/ml) of sonicated Eimeria tenella oocysts –SETO-ET), second group was immunized subcutaneously with 1 ml (1000 µg/ml) of sonicated Whole Cells Klebsiella pneumoniae antigen –SKWC-KP), third group was immunized subcutaneously with 1 ml (500 µg/ml of sonicated Eimeria tenella –SETO-ET and 500 µg/ml SKWC-KP). The fourth control group was injected subcutaneously by 1 ml of phosphate buffer saline. After 14 days all groups were given a booster dose at the same dose above. Results of Delayed type hypersensitivity showed that the third group had a high significant (P≤ 0.05) skin test reaction of Erythema and induration compared to the first and second groups after 24, 48 and 72 hours. Also, that was synchronized with the increased titers of antibodies, which increase to peak (720 ± 201.32) compared with the first group (200 ± 40.00) and second group (360 ± 100.66) after 35 days. This is the first study about the synergistic immune response interaction between Klebsiella pneumoniae and Eimeria tenella antigens in Iraq.